Scientific Literacy Competency Profile of Junior High School Students on Sustainable Energy - Himmah, Rif'atul; Jatmiko, Budi; Prahani*, Binar Kurnia; Saphira, Hanandita Veda (Jurnal IPA & Pembelajaran IPA, 2024)
The increasing demand for sustainable energy solutions presents a critical challenge that necessitates the development of scientific literacy among students. In response to this challenge, it is essential to develop students' understanding of sustainable energy. This study aims to analyze the science literacy profile of junior high school students on sustainable energy materials. A descriptive quantitative study was carried out in August 2024 at a State Junior High School in Kediri Regency, East Java, Indonesia with a sample of 130 grade VIII students. The research instrument was validated literacy test categorized as highly valid, with a reliability score of 92.14%, encompassing three PISA science competencies. The results showed that the majority of students from the sample had science literacy at the basic level or it can be said that it is in the low category with an average score of 49.00, where Students can only search for information in the science texts presented. The science literacy profile in the three competencies was also low, with an average score of 45.50% to explain scientific phenomena, 35.40% to design and evaluate research and interpret data, and 40.00% to research, evaluate, and use scientific information in decision-making. In conclusion, the science literacy of junior high school students is relatively low in all aspects tested, indicating the need for improvement in science learning, especially on the topic of sustainable energy